Analisis Proyeksi Harapan Lama Sekolah dalam Perspektif Maslahah: Studi Komputasi Grey GM(1,1) di Kota Palangka Raya - Zulya Desmita; Febrianto Afli; Robiatul Witari Wilda; Mega Yumia (ITB AAS INDONESIA Surakarta, 2026)
This research aims to analyze and project the direction of human capital accumulation in Palangka Raya City through the School Expectancy Length (SEL) indicator. Within the framework of Islamic economics, human capital accumulation is viewed as a fundamental instrument for achieving maslahah through the reinforcement of intellectual capacity (Hifdz al-Aql). This study employs a descriptive quantitative approach using secondary time-series data from the Central Bureau of Statistics for the period 2010–2025. Data analysis was conducted using the mathematical modeling of the Grey Forecasting Model GM(1,1), which is superior in predicting trends with limited data without relying on strict statistical distribution assumptions. The results indicate that this model has a very high level of accuracy with a Mean Absolute Percentage Error (MAPE) of 0.865%. Based on the projection results, the School Expectancy Length in Palangka Raya City is predicted to continue rising, reaching 15.47 years by 2030. Substantively, these findings confirm a consistent expansion of human capital, where the future school-age population is projected to be capable of attaining a Bachelor's degree level of education. The implications of this study emphasize the importance of policy synchronization between enhancing human resource capacity and providing strategic employment opportunities to ensure inclusive and sustainable economic welfare in Palangka Raya City.